Application of Spinal Disorders Detection on X-Ray Images Using Segmentation and K-Means Clustering - Khairul, Muhammad; Fauziah, Fauziah; Fitri, Iskandar (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2022)
There are three types of spinal disorders, namely kyphosis, lordosis, and scoliosis. To find out spinal disorders, it is necessary to carry out X-rays from an early age. Spinal disorders are not only found in children but can be found in adolescents, adults, and the elderly. Along with the times, making information technology more sophisticated is the advancement of image processing technology. Image processing can help in the medical field to analyze X-ray results to diagnose internal disorders or diseases. This study makes an application for the detection of spinal disorders with several methods of image segmentation processes and using the k-means clustering algorithm on x-ray images of spinal disorders. This segmentation image processing stage requires five stages of processing including cropping, resizing, median filter, histogram equalization, thresholding, and binary edges, and k-means clustering process as a comparison. This application is expected to be useful in knowing the difference between spinal disorders of lordosis, kyphosis, and scoliosis